Factors associated with risk of psychological problem among children of military personnel - Hassan, Hamiza (2017)
Background: There are many studies that reported the psychological impact of military deployment toward children of military personnel. The children of military personnel are at increased risk to develop psychological distress during the parental deployment. Objectives: The aim of this study is to determine Depression, Anxiety and Stress and its associated factors among children of military personnel in Kem Desa Pahlawan, Kota Bharu, Kelantan. Methods: A cross sectional study among 117 children of military personnel were conducted in April 2017, using the Malay translated and validated DASS-12 to detect Depression, Anxiety and Stress. Data were analyzed using multiple linear regressions.Results: 117 data were collected with the mean score of depression, anxiety and stress in the participants were 5.15(SD=2.52), 5.28(SD=2.54) and 5.44(SD=2.64) respectively. For depression, there is negative correlations with age (p<0.012) but positive correlations with duration of deployment (p<0.008). For anxiety, there is positive correlations with total monthly income (p<0.010) and duration of deployment(p<0.047). For stress, there is positive correlations with total monthly income (p<0.009) and duration of deployment (p<0.024). Conclusions: The finding suggest that depression is associated with age, gender, duration of deployment and the ability to contact of father. For stress and anxiety, it is associated with total monthly income and duration of deployment.